Perioperative management of a morbidly obese patient with Pickwickian syndrome who underwent herniotomy herniorrhaphy surgery - Reynaldi Reiky Hadiwijaya; I Made Gede Widnyana; Tjokorda Gde Agung Senapathi (Indoscholar, 2022)
Administering anesthesia in obese patients has its challenges. Most obese patients have multiple comorbidities with a higher risk for perioperative complications. Obese patients also have several physiological changes, including respiratory changes that could affect anesthesia. With the increasing number of obesity rates worldwide, the possibility of obese patients who need anesthesia increases, thus providing challenges for anesthetists in treating obese patients. This case described a 62-year-old male who underwent herniotomy and herniorrhaphy under general anesthesia. The patient was morbidly obese with a BMI of 54.68 kg/m2 and found to have Pickwickian Syndrome. The patient was assessed with physical state ASA III and underwent general anesthesia. The patient recovered with no complications and was discharged from the hospital three days after the surgery. In obese patients, several physiological changes could be a challenge for administering anesthesia. The choice of anesthetic agent for obese patients with Pickwickian Syndrome should be carefully selected, considering it can significantly impact the patient. The perioperative period should be focused on careful monitoring and improvement of comorbid diseases.